Edukasi Interaksi Obat dan Makanan dalam Mendukung Penggunaan Obat yang Aman pada Siswa SMK Farmasi Maharani Malang - Rebhika Lusiana; Amalia Rahmi; Nabilah Insani; Muhammad Rafli Habibi; Ihza Fadillah Rizky; Muhammad Alief Syekhan; Titania Tianka Albaniray; Ismi Abida; Salsabilla Aghnia Nazzala; Aqila Nurunnailah; Anjeli Oktaviana Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This counseling activity aimed to increase awareness and understanding of students at SMK Farmasi Maharani Malang regarding drug–food interactions in supporting the safe and appropriate use of medicines. Limited knowledge about drug–food interactions among adolescents may lead to reduced therapeutic effectiveness, increased risk of side effects, and inappropriate medication use. Therefore, educational activities are necessary to provide accurate information about the influence of food on drug therapy. The implementation method consisted of several stages: (1) a pre-test to assess students’ initial knowledge regarding drug food interactions; (2) an educational session delivered through PowerPoint presentations accompanied by interactive discussions and an educational crossword puzzle activity using printed media; and (3) a post-test to evaluate the improvement in students’ understanding after the educational intervention. Both the pre-test and post-test were conducted independently using Google Forms. The activity was carried out on Monday, December 1, 2025, and involved Grade XII students of SMK Farmasi Maharani Malang. The evaluation results showed an improvement in students’ understanding after participating in the educational activity. A comparison between pre-test and post-test results indicated an increase in students’ knowledge regarding types of drug–food interactions and safe medication use. This improvement demonstrates that the educational approach applied was effective in enhancing students’ medication literacy. It is expected that students who have gained this knowledge will be able to apply it in their daily lives and act as agents of change in disseminating accurate information about safe medication use to their families and communities.